Emotional intelligence: on the problem of defining the concept - E. N. Rastorgueva (Вестник университета, 2024)
The article is devoted to substantiate the need to clarify the definition of emotional intelligence (hereinafter referred to as EI). With consideration to the accumulated data on the neurophysiological foundations of EI and psychological trauma, as well as to the methods of psychotherapeutic work of various directions with human emotions and feelings, the introduction of a new element in the definition and structure of EI – emotional sensitivity (hereinafter referred to as ES) – is proposed and argued. ES is considered as the ability to focus attention on your emotions and feelings, be in contact with them, fully experience, be aware of them, immerse yourself into them, live deeply in safe conditions, distance yourself from them if necessary, and return to your experiences again. If the ability to realise one’s emotions and feelings is integrative, affective-cognitive in nature, then ES is the emotional basis of awareness of them, which is proposed to be distinguished separately as an independent and most important element of EI. In general, EI appears as an emotional-cognitive-personal education when the integrative essence of the concept, consisting in the unity of affective and cognitive processes of a person, is emphasised and reflected. In long-term psychotherapy, special and particular attention is given to the development of such an ability as ES. However, due to its important practical significance in people’s daily life, it should be showed in the definitions of EI and remembered in all forms of psychological work with a person.